2014
DOI: 10.1186/1556-276x-9-241
|View full text |Cite
|
Sign up to set email alerts
|

Nanofabrication on monocrystalline silicon through friction-induced selective etching of Si3N4 mask

Abstract: A new fabrication method is proposed to produce nanostructures on monocrystalline silicon based on the friction-induced selective etching of its Si3N4 mask. With low-pressure chemical vapor deposition (LPCVD) Si3N4 film as etching mask on Si(100) surface, the fabrication can be realized by nanoscratching on the Si3N4 mask and post-etching in hydrofluoric acid (HF) and potassium hydroxide (KOH) solution in sequence. Scanning Auger nanoprobe analysis indicated that the HF solution could selectively etch the scra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 26 publications
0
18
0
Order By: Relevance
“…Instead of operating AFM tips in contact mode, operating AFM tips in tapping mode to plow surfaces (dynamic plowing) [ 126 , 127 , 128 , 129 , 130 , 131 ] can also improve consistency in the fabricated features. The precision of the fabricated features has been improved by integrating mechanical removal with other approaches such as subsequent etching [ 132 ] or by introducing an intermediate resist layer [ 133 ] are demonstrated [ 133 , 134 , 135 , 136 , 137 , 138 ]. Recently, Yan et al demonstrated three-dimensional nanostructures with 100 nm lateral resolution [ 139 , 140 , 141 , 142 ] using these techniques.…”
Section: Overview Of Tip-based Nanofabrication (Tbn)mentioning
confidence: 99%
“…Instead of operating AFM tips in contact mode, operating AFM tips in tapping mode to plow surfaces (dynamic plowing) [ 126 , 127 , 128 , 129 , 130 , 131 ] can also improve consistency in the fabricated features. The precision of the fabricated features has been improved by integrating mechanical removal with other approaches such as subsequent etching [ 132 ] or by introducing an intermediate resist layer [ 133 ] are demonstrated [ 133 , 134 , 135 , 136 , 137 , 138 ]. Recently, Yan et al demonstrated three-dimensional nanostructures with 100 nm lateral resolution [ 139 , 140 , 141 , 142 ] using these techniques.…”
Section: Overview Of Tip-based Nanofabrication (Tbn)mentioning
confidence: 99%
“…Even though the wear scar generated at 90% RH was located, it is still hard to characterize the damage of silicon by conventional equipment (TEM) [ 17 , 18 , 19 ]. Since the etching rate on the surface of SiO x and Si(100) was significantly different in alkaline solution [ 20 , 21 , 22 , 23 ], the native oxide layer plays the role of etching mask for the substrate of Si(100) during the etching tests. Consequently, the Si(100) substrate would be quickly etched in alkaline solution if there was any damage on the native oxide layer.…”
Section: Resultsmentioning
confidence: 99%
“…According to the Arrhenius equation, the activation energy E a for the selective etching can be estimated as 0.33–0.38 eV in the present study. During the etching of silicon by KOH solution, silicon oxide film on silicon can resist the etching of KOH solution as a mask, and cause a slow etching rate at the beginning [ 10 ]. In this study, the native oxide layer on silicon was removed by HF solution before fabrication, and hence, it will lead to a rapid etching of silicon compared to the etching of bulk silicon surface [ 20 , 21 ].…”
Section: Resultsmentioning
confidence: 99%
“…Yu et al [ 9 ] proposed the friction-induced method to fabricate convex nanostructure on silicon surface with a diamond tip. Based on this, Guo et al [ 10 , 11 ] produced a series of protrusive hillocks with the height of hundreds of nanometers on silicon surface by the friction-induced selective etching. Furthermore, tribochemistry-induced selective etching can also produce defect-free nanostructures on silicon [ 12 , 14 ].…”
Section: Introductionmentioning
confidence: 99%